2023
DOI: 10.3390/jcm12123935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inflammation and Oxidative Stress Markers in Patients with Obstructive Sleep Apnea (OSA)

Maria Carmina Pau,
Angelo Zinellu,
Arduino A. Mangoni
et al.

Abstract: Background: The identification of circulating markers of oxidative stress and systemic inflammation might enhance risk stratification in obstructive sleep apnea (OSA). We investigated the association between specific haematological parameters, as easily measurable markers of oxidative stress and inflammation, and the degree of hypoxia during polysomnography using the apnea hypopnea index (AHI), oxygen desaturation index (ODI), and oxygen saturation (SpO2), in OSA patients. Methods: Associations between polysom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…For forward MR, we identified independent genetic variants in CIPs that reached genome-wide significance (p < 5×10⁻ 8 ), ie SNPs. However, the initial SNP selection using this criterion demonstrated limitations.…”
Section: Genetic Instrumental Variables (Ivs) Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…For forward MR, we identified independent genetic variants in CIPs that reached genome-wide significance (p < 5×10⁻ 8 ), ie SNPs. However, the initial SNP selection using this criterion demonstrated limitations.…”
Section: Genetic Instrumental Variables (Ivs) Selectionmentioning
confidence: 99%
“…However, the initial SNP selection using this criterion demonstrated limitations. Previous studies indicate the challenge of attaining the gold standard threshold of p < 5×10⁻ 8 for SNP selection in certain non-disease-related human phenotypes, such as gut microbiota, metabolic products, and immunological characteristics. Thus, for present MR analysis, setting the threshold between 5×10⁻⁶ and 5×10⁻⁵ is feasible.…”
Section: Genetic Instrumental Variables (Ivs) Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that NLR is associated with the severity of OSAHS. 23 Some research has investigated the relevance of SII and SIRI in the development of OSAHS 24,25 . However, there is currently no reported research on the relationship between MLR, PIV, and the occurrence of OSAHS, nor comparative studies of the association between different inflammatory parameters and the development of OSAHS.…”
Section: Introductionmentioning
confidence: 99%